Psychosocial Late Effects in Pediatric Cancer Survivors: A Report From the Children's Oncology Group. Issue 2 (21st October 2015) - Bitsko, Matthew J.; Cohen, Debra; Dillon, Robyn; Harvey, Jeanne; Krull, Kevin; Klosky, James L.
Abstract : Background: This review was conducted to update the Children's Oncology Group (COG) Long‐Term Follow‐Up Guidelines (COG‐LTFU Guidelines, version 4.0) regarding screening for psychosocial late effects of pediatric cancer. Procedure: Articles published between August 2009 and January 2011 that addressed psychosocial late effects of long‐term survivors of pediatric cancer (n = 35) were reviewed by a multidisciplinary team of COG late effect experts. Results: The majority of studies in this time period indicate that survivors experience few psychosocial problems in long‐term survivorship. A critical subset, however, is at increased risk for psychosocial late effects secondary to the treatment. Highlighted findings from this review include increased rates of suicidal ideation (SI), and health beliefs as robust predictors of SI, anxiety, and global distress. Survivors' health beliefs were associated with their perceptions of physical limitations, overall late effects, and cancer‐related pain. While many survivorship studies continue to specify risk factors for anxiety and posttraumatic stress symptoms/posttraumatic stress disorder, others outcomes (e.g., developmental, interpersonal, and familial factors) appear to be emerging in importance. Conclusions: Although the majority of childhood cancer survivors do not experience psychosocial problems, a subset will. The recent research findings have been included in the new COG‐LTFU Guidelines that will assist in the targeted assessment and the treatment of survivors' psychosocial health.